Soil water availability and water absorption by maize in sodic soils with high water table - Garello, Federico José; Ploschuk, Edmundo L.; Melani, Esteban; Taboada, Miguel Angel (Elsevier, 2023)
Context: Because of the increasing prices of commodities over the last decades, crops like maize (Zea mays L.) are being cultivated in lowland sodic soils with physical-chemical constraints, such as those having natric horizon (Btn); however, the magnitude of the reductions in maize productivity in the face of these limitations under different water regimes is not known. Maize is a highly water-demanding crop in midsummer, so the ability of the Btn horizon to provide enough water to the crop in times of high atmospheric demand is still unclear. Objective: The objectives were to evaluate (i) the contribution of the Btn horizon to water absorption by maize, and (ii) the effect of soil exchangeable sodium percentage (ESP) in the Btn horizon on leaf area index (LAI) and maize grain yield (GY) under contrasting imposed soil water conditions. Methods: Field trials were carried out during the growing seasons 2018/19 and 2019/20 at Chascomús, Argentina (35º 44′ S; 58º 03′ O), where sodic soils with natric horizons and high-water table are plentiful. Treatments included a bare soil without cultivation and maize crops under two water regimes: i) rainfed control (C), ii) drought (D), under a wide range of exchangeable sodium percentage (ESP) in the Btn horizon (from ESP 3–34 %). Results: Maize crops could uptake water from the Btn horizon in both water regimes (C and D), but absorption decreased by ≈ 1 % for every 1 % increase in subsoil ESP. This increase in sodicity also decreased the LAI by 0.053 cm cm−2, and GY by 134.5 kg ha−1. In the treatment with imposed drought, maize roots passed down the Btn horizon and reached the groundwater from where they absorbed water. Conclusions: The Btn horizon can be considered a source of water for the maize crop, mainly with low levels of ESP. The detrimental effect of ESP in the GY was independent of water regimes in the crop cycle. SIGNIFICANCE: These results are useful for farmers to adjust crop management, considering the soil ESP, available water in the Btn horizon, and the groundwater depth, making use of water and soil resources more efficient and sustainable.